2015
DOI: 10.1136/jclinpath-2015-202961
|View full text |Cite
|
Sign up to set email alerts
|

Decreased argyrophilic nucleolar organiser region (AgNOR) expression in Purkinje cells: first signal of neuronal damage in sudden fetal and infant death

Abstract: AimsThe nucleolus is an important cellular component involved in the biogenesis of the ribosome. This study was performed in order to validate the introduction of the argyrophilic nucleolar organiser region (AgNOR) stain technique, specific for the nucleoli detection, in neuropathological studies on sudden fetal and infant death.MethodsIn a wide set of fetuses and infants, aged from 27 gestational weeks to eight postnatal months and dead from both known and unknown causes, an in-depth neuropathological study u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 38 publications
0
7
0
1
Order By: Relevance
“…Our previous studies have reported on an array of important side effects of nicotine exposure on the developmental process of the different brainstem centers essential for life (Lavezzi, Ottaviani, Mingrone, et al., 2005; Lavezzi, Ottaviani, Matturri, 2005; Lavezzi et al., 2007; Lavezzi et al., 2013; Lavezzi, Ferrero, et al., 2016). The findings of our study add new insights to this field and highlight the fact that the altered expression of nAChR, also limited to CC, puts fetuses exposed to maternal cigarette smoking in utero, at higher risk of SIDS or SIUDS.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies have reported on an array of important side effects of nicotine exposure on the developmental process of the different brainstem centers essential for life (Lavezzi, Ottaviani, Mingrone, et al., 2005; Lavezzi, Ottaviani, Matturri, 2005; Lavezzi et al., 2007; Lavezzi et al., 2013; Lavezzi, Ferrero, et al., 2016). The findings of our study add new insights to this field and highlight the fact that the altered expression of nAChR, also limited to CC, puts fetuses exposed to maternal cigarette smoking in utero, at higher risk of SIDS or SIUDS.…”
Section: Discussionmentioning
confidence: 99%
“…Murgod et al reported a significant increase in the number of AgNOR in oral submucosal fibrosis and squamous cell carcinoma. Lavezzi et al used the number of AgNOR in the detection of neuronal damage in newborns. Eröz et al stated that the number of AgNOR in hair follicles increased with the effect of growth hormone.…”
Section: Discussionmentioning
confidence: 99%
“…Na slici 1 apeks krivulje učestalosti AgNOR publikacija, u kojima se prvenstveno radi o tumorskoj patologiji, ukazuje na nagli porast interesa za funkciju ribosomalnih gena u onkogenezi i uvod je u istraživanje jezgrice dinamičkim molekularnim metodama na ulazu u 21. stoljeće kada dolazi do promjene definicije jezgrice. Povezivanjem oblika, strukture i funkcije AgNOR metoda ukazuje na razvoj znanstvene misli, te daje uvid u povezanost jezgrice s patološkim stanjima koja su danas opisana molekularnim metodama [76][77][78][79][80]111,[122][123][124][125][126][127][128][129][130][131][132] . Time patologija, molekularna biologija i biotehnologija dobivaju zajednički cilj istraživanja: jezgricu u bolesti, što je vidljivo i ovdje u slici 1 i 2, a u čemu među prvima sudjeluju znanstvenici Medicinskog fakulteta u Rijeci 132 .…”
Section: Grupa Za Agnor I Rezultati S Apeksomunclassified